Real World Data Estimation: Management and Cost-analysis of Stroke in Tertiary Hospitals in Turkey and the Impact of Co-morbid Malnutrition - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2016)
Objective: To evaluate the management and cost analysis of first-ever stroke patients in Turkey and determine the impact of comorbid malnutrition. Methods: This study was based on expert's view on the management and cost analysis of stroke patients with or without malnutrition via standardized questionnaire forms filled by experts according to their daily clinical practice. Cost items were related to medical treatment, healthcare resources utilization, tests, consultations and complications. Per admission and total annual direct medical costs were calculated with respect to co-morbid malnutrition. Results: Malnutrition was evident in 7.8(3.6)% [mean(standard error of mean; SEM)] of patients at admission; an additional 7.1(4.8)% and 0.9(0.6)% patients developed malnutrition during Neuro-ICU and stroke unit hospitalization, respectively. Length of hospital stay (LOS) was almost 2-fold in patients with malnutrition (P<0.01 for all hospital units). During the 1-year follow-up period a mean(SEM) of 93.8(15.4)% with and 43.3(3.7)% without malnutrition were expected to experience at least 1 complication. The mean (SEM) per patient annual cost of stroke was US$5201(740) in patients with malnutrition and US$3619(614) in patients without malnutrition, while the corresponding figures for per admission were US$3061(513) and US$1958(372), respectively. Conclusions: In conclusion, our findings revealed that management of stroke and its complications have a relatively high burden on the Turkish health reimbursement system. Furthermore, co-morbid malnutrition, being not uncommonly encountered, increased the overall costs and was associated with longer LOS and higher rate of expected complications during 1-year follow up.
Keywords: Stroke; malnutrition; cost analysis; direct medical cost; diagnosis; treatment; follow up; Turkey; expert panel; ACUTE ISCHEMIC-STROKE; LENGTH-OF-STAY; NUTRITIONAL RISK; CEREBROVASCULAR EVENTS; HEMORRHAGIC STROKE; INPATIENT COSTS; CARE; UNDERNUTRITION; MORTALITY; OUTCOMES